ECONOMIC VIABILITY OF CORN CROP AS FUNCTION OF DOSES, FORMS AND APPLICATION TIMES OF NITROGEN IN BRAZILIAN SAVANNAH - Fernando Shintate Galindo (Tropical and Subtropical Agroecosystems, 2019)
Alternatives to reduce losses of nitrogen (N) in the soil, increasing the use of the plant nutrient efficiency are important depending on N dynamics in the soil, to increase their use and achieve high yields economically profitable. In this context, economically-analyzed whether the effect of the mechanical application of N doses as urea, in different forms and times of application, in the grain yield of corn in Cerrado region with low altitude (Brazilian Savannah). The experiment was conducted in Selvíria – state of Mato Grosso do Sul, an Oxisol clayey, in 2013/14. The experimental design was a randomized complete block design with four replications, in a factorial 6 x 2 x 2, as follows: 6 N doses (0, 50, 100, 150, 200, 250 kg ha-1), 2 application times (totally in sowing or topdressing) and 2 application forms (surface or incorporated) of N, analyzing total operacional cost (TOC), effective operacional cost (EOC), gross revenue (GR), operating profit (OP), profitability index (PI), equilibrium price (EP), and equilibrium yield (EY). The urea application at a dose of 150 kg ha-1, fully applied at sowing and surface provides greater profitability in irrigated maize, ensuring profitability with production of grains in the Cerrado with low altitude.